The new physics reach of null tests with $$D → π \ell \ell $$ D→πℓℓ and $$D_s → K \ell \ell $$ Ds→Kℓℓ decays - Rigo Bause; Marcel Golz; Gudrun Hiller; Andrey Tayduganov (European Physical Journal C: Particles and Fields, 2020)
Abstract $$|Δ c|=|Δ u|=1$$ |Δc|=|Δu|=1 processes are unique probes of flavor physics in the up-sector within and beyond the Standard Model (SM). SM tests with rare semileptonic charm meson decays are based on an approximate CP–symmetry, a superior GIM–mechanism, angular distributions, lepton-universality and lepton flavor conservation. We analyze the complete set of null test observables in $$D → π \ell \ell ^{(′ )}$$ D→πℓℓ(′) and $$D_s → K \ell \ell ^{(′ )}$$ Ds→Kℓℓ(′) decays, $$\ell ^{(′ )}=e, μ $$ ℓ(′)=e,μ , and find large room for new physics safely above the SM contribution. We identify signatures of supersymmetry, leptoquarks and anomaly-free $$U(1)^′ $$ U(1)′ –models with generation-dependent charges, for which we provide explicit examples. $$Z^′ $$ Z′ –effects in $$c → u \ell \ell ^{(′ )}$$ c→uℓℓ(′) transitions can be sizable if both left-handed and right-handed couplings to quarks are present.